Odpowiedzi

Najlepsza Odpowiedź!
2009-10-24T20:43:23+02:00
(x²+1) :4 + (x² + 1) : 2= -x²:4 /4
4(x²+1):4 + 4(x²+1):2 = 4 × -x²: 4
x²+1+2x²+2= -x²
3= -x²-2x²-x²
3= -4x²/: -4x
x= -¾x
x+ ¾x= 0
1¾x= 0/:1¾
x=0
Odp. Jest to równanie tożsamościowe, czyli rozwiązaniem tego równania może być każda liczba.
Pozdrawiam ;)
2009-10-24T21:01:17+02:00
(x²+1) :4 + (x² + 1) : 2= -x²:4 /4

4(x²+1):4 + 4(x²+1):2 = 4 × -x²: 4

x²+1+2x²+2= -x²

3= -x²-2x²-x²

3= -4x²/: -4x

x= -¾x

x+ ¾x= 0

1¾x= 0/:1¾

x=0
2009-10-24T21:02:47+02:00
( x- 1)² : 4 - (x+1)² : 2 = -x² : 4

( x- 1)² : 4 - (x+1)² : 2 = x² - 1 : 4 - x² + 1 = ( x² - x² ) : 4 - ( 1 + 1 ) = 0 :4 - 0 = 0